Comparative Vertebrate Lateralization 2002
DOI: 10.1017/cbo9780511546372.011
|View full text |Cite
|
Sign up to set email alerts
|

Posture and laterality in human and non-human primates: Asymmetries in maternal handling and the infant's early motor asymmetries

Abstract: This chapter is concerned with the question of the relations and possible influences of environmental factors on the establishment of patterns of manual lateralization in human and non-human primates. More specifically, we are interested in the relation between maternal postures and laterality in nonhuman primates (e.g. bias in cradling behaviour and hand preference of the mother) and the development of patterns of manual preferences in infants. In order to understand fully the many ways in which these variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 84 publications
(155 reference statements)
2
31
2
1
Order By: Relevance
“…Several studies in humans showed that females have a left-sided cradling bias while males do not (Damerose and Vauclair, 2002). If we assume that a similar sex difference is evident in chimpanzees and gorillas, which would be difficult to determine because most males show little infant cradling, then whatever social or genetic factors selected for left-sided cradling was retained in human evolution as manifest in the extant sex differences seen in modern humans.…”
Section: Cradlingmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies in humans showed that females have a left-sided cradling bias while males do not (Damerose and Vauclair, 2002). If we assume that a similar sex difference is evident in chimpanzees and gorillas, which would be difficult to determine because most males show little infant cradling, then whatever social or genetic factors selected for left-sided cradling was retained in human evolution as manifest in the extant sex differences seen in modern humans.…”
Section: Cradlingmentioning
confidence: 92%
“…Several investigators have reported evidence of laterality in cradling biases in nonhuman primates, which are summarized in Table I (Damerose and Vauclair, 2002). It was not always clear whether a distinction was made by some authors between maternal cradling and infant positional biases (Table I).…”
Section: Laterality For Maternal Cradling and Infant Positional Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…laterality; mother-infant behavior; cradling; nipple preference Damerose and Vauclair (2002) and Hopkins (2004) recently suggested that early asymmetries in mother-infant behaviors may be the basis for the development of handedness. In particular, Hopkins (2004) argued that infant primates are not born into symmetrical environments but instead are exposed to imposed asymmetries by the caretaker, in the form of cradling biases, or the infants show explicit asymmetries in reflexive behaviors such as head orientation or limb strength (Fagot and Bard, 1995;Hopkins and Bard, 1995;Hopkins et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, humans, particularly women, show universal left-sided biases in cradling infants (Damerose and Vauclair, 2002). Researchers have reported a similar left-sided maternal cradling bias in great apes, notably in chimpanzees and gorillas, but not in other primates (Cunningham et al, 1989;Damerose and Vauclair, 2002;Dienske et al, 1995;Fischer et al, 1982;Hopkins, 2004;Lockard, 1984;Manning and Chamberlain, 1990;Manning et al, 1994;Rogers and Kaplan, 1995; Toback, 1999). Evidence of asymmetries in other early mother-infant behaviors of primates, such as nipple preferences, is less clear.…”
mentioning
confidence: 99%